Implementation of Business Intelligence In Planet Helmet Cilacap Sales - Setiani, Ginanjar Rizqi; Verry, Verry; Abdul Aziz Zein, Mochamad Taufiqurrochman (Brilliance: Research of Artificial Intelligence, 2024)
Helmets are used to anticipate serious injuries when traffic accidents occur. In several cities and villages, various helmet businesses have begun to emerge. The increasing number of residents and motorized vehicles in Indonesia provides business opportunities in the helmet business. The increasingly competitive business market challenges companies to be able to adapt to changing market conditions and diverse buyer needs. For this reason, companies must be able to respond quickly and accurately, consider the costs incurred to remain conducive, and have a strategy in decision-making that can provide solutions to changes in the current market situation to survive in the long term. Therefore, companies must be able to respond quickly and accurately, consider the costs incurred to remain conducive, and have a strategy in decision-making so that companies can survive in the long term. The implementation of business intelligence in this study uses the Online Analytical Processing (OLAP) method, namely the use of Extraction Transformation Loading (ETL), creating a data warehouse, analyzing data for users and user interfaces in the form of information visualization using the Laravel framework. Planet Helm currently needs to manage its sales data visualization digitally. This is an obstacle for leaders in managing inventory needs, and helmet sales are less effective and efficient, requiring the digitalization of web-based business intelligence management. The results of this study are in the form of a dashboard display consisting of a minimum of 7 stock widgets, average monthly sales, popular brand graphs, and monthly sales graphs.